Recent development in continuous water quality monitoring technologies and applications - A. Bakar Jaafar; S.L.Tong; N. Suhaila Othman; Amirul Shazli Mohamed (Environmental Management Society, Malaysia, 2000)
One of the weak links in water Quality management is its dependence on traditional manual grab water sampling which provides only limited information on the status and trends of the water body. As a remediation continuous water quality monitoring using multi-parameter sondes or auto analysers which generate continuous and real-time water quality data at fixed locations have found increasing applications in recent year. More recently, interests have been extended to develop techniques for obtaining continuity in the spatial dimension of the water quality information. This paper briefly reviews the recent development in these areas. The paper will focus on reporting on the general features of the continuous water quality monitoring stations under the National Water Quality Monitoring programme of the Department of Environment for ten rivers in Malaysia, established and operated by Alam Sekitar Malaysia Sdn. Bhd (ASMA) since late 1996. The system instrumentation and telemetry configuration, emphasizing on cost-effectiveness and minimizing maintenance constraints, are presented. The application of the large volume of water quality data generated for river management is illustrated through highlights of the significant findings for two rivers, namely, Sg. Linggi and Sg. Sarawak